Pelatihan Penyelenggaraan Jenazah di Desa Bilanrengi Kecamatan Parigi Kabupaten Gowa - Khaerul Aqbar; Sirajuddin Sirajuddin; Azwar Azwar (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2022)
The Community Service Program (KKN) Batch V of STIBA Makassar students aims to increase the Islamic knowledge and religious skills in the people of Bilanrengi Village, Parigi District, Gowa Regency, especially in organizing of corpse according to Islamic law. Implementation of activities begins with mapping problems and needs using SOAR analysis. After analyzing the problems and needs, work programs are then prepared according to the needs of the community. The work program that was successfully implemented was the Training of Corpse Organizing. The method used is in the form of lectures, discussions, and practice, with the stages of PkM activities, namely: the observation, preparation, training, mentoring, and evaluation. The result of this activity was the amount of enthusiasm and support from the community for the training activities, especially elements from the village administration, village priests, taklim assemblies, and the community, especially ladies and gentlemen. The community feels great benefits after participating in this KKN program, including an increase in knowledge, insight and religious skills, especially related to organizing the human corpse in accordance with Islamic teachings. The continuation of this program is in the form of further coaching for participants, especially training on handling abnormal corpses, such as corpses with certain diseases, accident victims, victims of natural disasters, and others, which require special and different treatment from corpses in general.